Cotidiano de teatro de grupo no Cariri cearense: ninho de teatro e coletivo atuantes em cena - Matias, Bárbara Leite (2017)
The present work analyzes the artistic-teaching practices of two theater groups in Ceará, located specifically in the Cariri region. The groups are as follows: Coletivo Atuantes em Cena (Juazeiro do Norte) and Ninho de Teatro (Crato). In this research we have a panorama of situations that encompass the experience and daily life of these theater groups, considering that all members of both groups are artist-educators. In the course of the research we intend to verify the specific characteristics of the artist-teacher in these two spaces of theatrical work.